Hydrogeochemical Characterization and Numerical Flow Modeling of the Ujjain Aquifer System - Vashum, Themchuiso (Journal of Progress in Civil Engineering, 2026)
Water – water - water its one of the most precious Compound present on Earth. Without water life is not possible in any means. The history depicts that human beings are also water born, that’s why we our self own 70% of water in our body. On earth we have tremendous amount of water available but not for drinking. Generally for drinking water we have limited ourselves in either fresh surface water or ground water. The ground water has its own place in our daily life no matter it’s from a dug well or bore well. In Ujjain city we have about 33, 390 dug wells and about 47, 755 bore wells/ tube wells, these are large numbers comparing to a B class city but still their misuse happens and the city is thirsty and we look in hope for the Public Health Engineering (P. H. E.) department to supply 11M. L. D. (Million Liters per Day) water to fulfill the needs of city. In this research we have selected 7 different bore wells across the city area and analyzed their Physico chemical parameters for drinking water. General overview of our result is that the water of these bore wells is very good for drinking and the parameters value are well within the limits. We in this research also propose a ground water model to predict the hydrological changes of the local area and also give the mathematical equations and solutions for this model. Application of this model will increase the ground level of water. This will lead to the abundance of drinking water will be available to local people of Ujjain.